Visualization of molecular stacking using low-energy electron microscopy - Procházka, Pavel; Čechal, Jan (Ultramicroscopy, 2023)
The design of metal-organic interfaces with atomic precision enables the fabrication of highly efficient devices with tailored functionality. The possibility of fast and reliable analysis of molecular stacking order at the interface is of crucial importance, as the interfacial stacking order of molecules directly influences the quality and functionality of fabricated organic-based devices. Dark-field (DF) imaging using Low-Energy Electron Microscopy (LEEM) allows the visualization of areas with a specific structure or symmetry. However, distinguishing layers with different stacking orders featuring the same diffraction patterns becomes more complicated. Here we show that the top layer shift in organic molecular bilayers induces measurable differences in spot intensities of respective diffraction patterns that can be visualized in DF images. Scanning Tunneling Microscopy (STM) imaging of molecular bilayers allowed us to measure the shift directly and compare it with the diffraction data. We also provide a conceptual diffraction model based on the electron path differences, which qualitatively explains the observed phenomenon.
Keywords: Low-energy electron microscopy; Layer stacking; Dark-field contrast; Self-assembly